Intolerance predicts climate skepticism - Alva Johansson; Niclas Berggren; Therese Nilsson (Research Institute of Industrial Economics (IFN), 2021)
While there is almost unanimous consent among scientists that climate change is real and has detrimental consequences, there is a sizable number of people who are skeptical towards these propositions and who are not worried by climate change. In an attempt to understand the basis of climate skepticism, we look at the role of intolerance, a culturally transmitted attitude to the effect that people with certain characteristics are not to be respected. The theoretical link from intolerance to climate skepticism is driven by two elements: insufficient or biased knowledge formation and a value of not caring very much about the welfare of others. Our empirical analysis confirms that intolerance on the basis of race, ethnicity, immigration status, religion or sexual orientation predicts climate skepticism. By using the epidemiological method, relating the views on climate change of second-generation immigrants in Europe to cultural values in their countries of origin, we are able to rule out reverse causality - a novelty in the literature trying to explain climate skepticism. To get a feeling for the importance of intolerance, an increase in the share who are intolerant towards people of a different race in the individual's country of origin by 10 percentage points implies a reduced probability of the individual considering the consequences of climate change extremely bad of 4.3 percentage points (21.5%). An important implication of our findings is that to influence climate skeptics, it may be necessary to go beyond argumentation about the facts as such and to find ways to affect more basic individual characteristics.
Keywords: F64; Q01; Q54; Z10; 330; Climate skepticism; culture; intolerance; causality; values